Systematic Review of Trends in Dark Tourism Research - Siti Hamidah; Hakim, Imam Nur (Universitas Airlangga, 2023)
Dark tourism, encapsulating themes of death, crime, violence, and suffering within a tourism framework, has sparked controversy and ethical concerns. Nevertheless, it remains a compelling subject of research. This study employs the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol to provide a systematic overview of the trends in dark tourism research disseminated across reputable Scopus scientific journals over the last decade. The findings present a comprehensive snapshot of the evolving landscape of dark tourism research, identifying key variables that signify the expansive realms open for exploration within this domain.